Analisis Lingkungan Kerja dan Motivasi Karyawan di PT Sipatex - Fauzi, Ari Mohamad; Tresnawati, Amilia (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study examines the relationship between work environment and employee motivation at PT Sipatex, a textile company in Bandung. The main issue addressed is the significance of motivation as a key factor in improving productivity and company competitiveness, as well as how the quality of the work environment influences motivation. The research employs a descriptive qualitative method, collecting data through in-depth interviews with five employees, direct observation in the production area, review of company policy documents, and focus group discussions (FGD). The findings indicate that a supportive work environment, both physically (lighting, cleanliness, comfort) and socially (interpersonal relationships, managerial support), plays an important role in enhancing work motivation. Adequate facilities, effective communication, and opportunities for self-development are identified as the main motivational drivers. The study concludes that continuous evaluation and improvement of the work environment are strategic efforts to boost employee motivation, loyalty, and productivity. These findings provide practical contributions to company policy development and human resource management in the manufacturing sector.